Solve for x log(base6)(x+3)−log(base6)(x−5)=2.

I tried to factor out the log(base6) and got (x+3)^x/(x-5)=2, but I don't know how to solve that...

4 answers

sorry it's log(base6)(x+3)−log(base6)(x−5)=2

the x in front of log isn't part of it
Oh no, 6 is not a number, it is an operator.

You can't factor out 6
(that would be doing something like
√8 - √3
= (√)(8-3) )

You have to use your rules of logs.

6(x+3) - 6(x-5) = 2
6 ( (x+3)/(x-5) ) = 2

which by definition is
(x+3)/(x-5) = 6^2 = 36
36x - 180 = x+3
35x = 183
x = 183/35
Oh no, log6 is not a number, it is an operator.

You can't factor out log6
(that would be doing something like
√8 - √3
= (√)(8-3) )

You have to use your rules of logs.

log6(x+3) - log6(x-5) = 2
log6 ( (x+3)/(x-5) ) = 2

which by definition is
(x+3)/(x-5) = 6^2 = 36
36x - 180 = x+3
35x = 183
x = 183/35
thank you for your explanation :)
Similar Questions
  1. prove:1/log(base36)a = 2/log(base6)a i made a common base and then multiplied both sides with log(base6)a to get
    1. answers icon 1 answer
    1. answers icon 5 answers
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions